2023
DOI: 10.1002/mnfr.202200709
|View full text |Cite
|
Sign up to set email alerts
|

Barley Phenolamides Effectively Scavenge Harmful Methylglyoxal In Vitro and in Mice

Abstract: Scope: Methylglyoxal (MGO), a harmful reactive dicarbonyl, is involved in the pathogenesis and development of diabetes and diabetic complications. The goal of this study is to determine whether bioactive phenolamides in barley, p-coumaroylagmatine (pCAA) and feruloylagmatine (FAA), which share a similar guanidine group to diabetic drug metformin, have the capacity to detoxify MGO. Methods and results: In this study, the MGO-trapping abilities of these two phenolamides both in vitro and in mice are evaluated. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
2
1
0
Order By: Relevance
“…In addition, we found that biological activities of identified key metabolites that were enriched by NSND processing have consistently been proved in previous studies, 28,52,55,57,65,67,73‐78 supporting our findings (Table 3). Among them, gallocatechin and furoaloesone showed the largest binding energy with most of the targeted proteins.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, we found that biological activities of identified key metabolites that were enriched by NSND processing have consistently been proved in previous studies, 28,52,55,57,65,67,73‐78 supporting our findings (Table 3). Among them, gallocatechin and furoaloesone showed the largest binding energy with most of the targeted proteins.…”
Section: Resultssupporting
confidence: 91%
“…We conducted molecular docking to further investigate the binding ability between key targets – that is, TNF, VEGF, STAT3, IL6, STOR, GCKR, GLIT4, HIF1, and INSR – that were closely related to oxidative stress, inflammation, and hyperglycemia, and 13 main metabolites that were significantly abundant in aqueous extracts of processed PK compared with crude PK. Results collectively demonstrated great ability of processed PK‐enriched metabolites to combat abnormal oxidative stress and inflammation status, as well as hyperglycemia, partly via regulating multi‐pathways, consistent with previous study 28,63‐70 …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation